The Quality of Information System Applications and Service Quality Increases Customer Satisfaction - Napitupulu, Ilham Hidayah; Rima Rachmawati; Rini Lestari (MIMBAR : Jurnal Sosial dan Pembangunan, 2023)
Abstract. This paper examines the quality of service and the quality of online motorcycle taxi system applications that can affect consumer satisfaction during the Covid-19 pandemic. This research is the development of the TAM concept that provides hope, and can help to predict user attitudes and acceptance of information system technology. The user's perception of the application system depends on the quality of the information system available, where the quality measures of the online application system are Reliability, Flexibility, Security, Easy to use, Privacy, Accessibility. This research is a survey research using a questionnaire as a source of processed data. Determination of the research sample using justment sampling. Questionnaires were distributed to respondents using the online motorcycle taxi application, in this case GOJEK, as many as 340 respondents. Research data were analyzed using multiple linear regression with SPSS tools. The results of the study explain that only flexibility has no effect on customer satisfaction, while service quality, Reliability, Security, Easy to use, Privacy, Accessibility have an effect on customer satisfaction. Using the TAM concept, online motorcycle taxi providers can retain old customers and find new customers by conducting surveys at certain periods of online motorcycle taxi users' consumers.